Court of the Flowers, Rainbow Girl atop Fountain of Life, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
At the pinnacle of the Fountain of Life in this beautiful and restful crimson colored Court of the Flowers is the Rainbow Girl, who plucks a Rainbow from the Sky. The base of fountain is dotted with statuettes and a luxuriant growth of flowers.